Grid‐connection analysis of hydro‐turbine generator unit with stochastic disturbance. Issue 3 (17th January 2019) - Liu, Jing; Xu, Beibei; Chen, Diyi; Li, Jianling; Gao, Xiang; Liu, Gongcheng
Abstract : Here, the authors bring attention to the stability of the hydro‐turbine generator unit (HTGU) with stochastic disturbance during the grid‐connection process. First, the stochastic factor of the water head is innovatively introduced to the hydro‐turbine governing system (HTGS) during the start‐up process of the HTGU. Then, the dynamic characteristics of the start‐up and grid‐connection process are studied under different stochastic intensities and different values of three system parameters by two different methods, in detail. The results show that the stability of grid‐connection is affected obviously by the various intensities of stochastic water head, and there are some interesting phenomena and significant laws. Meanwhile, the values of the HTGS parameters show certain effect on the resistance of HTGS to the stochastic disturbance. Finally, this study can provide a theoretical basis for improving the probability of success in combining the HTGU to the grid in practical process.